FUTILITY AND THE OBLIGATIONS OF PHYSICIANS - Wilson, Bradley E. (Bioethics, 1996)
It is becoming increasingly common (at least in the United States) for doctors to appeal to futility judgments as the basis for certain types of clinical decisions, such as the decision to withhold CPR. The clinical use of futility judgments raises two basic questions regarding futility. First, how is the concept of futility to be understood? Secondly, once we have a clearer understanding of futility, what role should determinations of futility play in clinical decision-making? Much of the discussion about the concept of futility has centered on the value-ladenness of futility judgments. I argue that futility determinations need to be distinguished from two other types of value-based judgments, namely, identification of the goals of treatment and treatment decisions based on an assessment of the benefits and burdens of treatment. If this distinction is sound, it suggests a very limited role for futility determinations in clinical decisionmaking, a role which should serve to promote communication between doctor and patient.